Pengaruh Media Botolsis Smash terhadap Teknik Smash Forehand dan Backhand Tenis Meja Siswa SMP - Waris, Achmad; Putri, Wahyu Setia Kuscahyaning; Cahyani, Olivia Dwi (Jurnal Porkes, 2026)
Mastering forehand and backhand smash techniques in table tennis remains a challenge for junior high school students, mainly due to the limited availability of learning media that is interesting, simple, and supports repetitive practice. This study aims to examine the effectiveness of the innovative Botolsis Smash learning media, which utilizes used bottles and height-adjustable tripods, in improving students' forehand and backhand smash skills in table tennis. The method used was a quasi-experiment with a one-group pretest-posttest design, involving 30 eighth-grade students from SMPN 1 Sumberrejo as research subjects. Data were obtained through a smash skill test that had been tested for validity and reliability, then analyzed statistically using a paired sample t-test using SPSS version 30. The results showed a significant increase in backhand smash (p < 0.001) and forehand smash (p < 0.001) skills, with higher posttest scores compared to pretest scores. The conclusion of this study indicates that the Botolsis Smash is effective as a contextual, economical, and applicable training tool in improving basic table tennis techniques, thus serving as an alternative teaching medium for physical education in schools.